دراسة بعض الخواص الفيزيائية لمتراكبات بوليمرية المستخدمة في بيئة كيمياوية سلبية - عباس رولا عبد الخضر (Al-Nahrain Journal of Science, 2010)
Study was a reflection of the impact of theextensive use of overlapping materialspolymer composed of material of glass fiberreinforced epoxy in the center of bothcontaminated with chemicals (acid and base)on the physical properties, which included(Hardness, resistance to compressionCompressive Strength, compressiondeformation and deformation Compressive,and absorbed the maximum amount of acidsolution or basal M∞, and diffuse (Diffusivity)D), as evidence of the importance of chemicalsas one of the sources of pollution whichcontribute directly or indirectly in the processof aging of these materials overlapped. And itwas also to examine the factors accelerated theprocess of chemical aging here (chemicalnature and concentration, as well astemperature and immersion time of it) andhow these impact on the efficiency ofaccelerators functioning with accumulation inthe composite body prepared. Note that thearticle supported Overlapping prepared anumber of plywood sheets authority matchopped glass fiber (chopped mat strand) andthe (6,8,10,12) layer for composite materialsdifferent volumetric fraction of fiberreinforcement ranged between (53.3-20%),and the solution pH elected for this study wereacetic acid and a potassium hydroxide, whichranged between standard (2-0.5N), or a greaterconcentration of potassium hydroxide byweight up to about (10.2-2.8%), while equivalent to increasing the concentration ofacetic acid per volume of up to about (15-3.757%). The comparison results showed thatincreasing the concentration of the chemicalquality of the center (acid and base), andtemperature, which ranged between (14 to60)0C in addition to the time of immersion,and not more than (34) hours, all of whichhave a negative impact on the hardness andresistance to compression, Because thesecommunities as they enter the body polymercomposite accumulate year after year to beharmful to focus composite materials andproperties caused by the overlapping agingmaterials prepared and it seems clear from theincrease in assessed compression deformationand the amount of swelling maximum. Theresearch also found the results are obvious andclear that it could delay the process ofincreasing the number of layers of limitationfiberglass reinforced epoxy material whichaccompanied the process of delay does notappear to unforeseen damage to the third eyein the article is strikingly overlapped with thevolumetric fraction (29%) compared with themodel is the volumetric fraction (20%) whenplaced in a standard acid solution (2N) andtemperature (140C). Accordingly, use ofphotography to document these macroscopicdamage observed in the article overlappedwith the volumetric fraction (20%), whileensuring that the optical microscopy imagingto monitor the damage was not seen by thenaked eye with the film surfaces and the partsaffected side and the article generated in theoverlapped with the volumetric fraction (29 %).The result of the extensive use of overlappingin the center base to accelerate the process isfaster than aging medium acid.